ESTUDO E OTIMIZAÇÃO DO PROCESSO DE PRODUÇÃO DE BIODIESEL METÍLICO DE ÓLEO DE COCO BABAÇU COM AQUECIMENTO POR MICROONDAS USANDO UM DELINEAMENTO COMPOSTO CENTRAL ROTACIONAL (DCCR). - Nascimento, Ulisses Magalhães (2008)
Generally, the organic reaction heating under microwave irradiation reported reduced reaction time and larger yield. Therefore, way was sought in this work to study and to optimize the transesterification reaction used in biodiesel production with methanol and heating for irradiation microwave using coconut babassu oil. It was used a Central Rotatable Composite Design (CRCD) symmetrical and of second order, constituted of two parts: the factorial 2n, with an or more central points, and the axial part., varying the reaction time, concentration of KOH and ratio oil:methanol. With base in this factorial planning, surfaces and curves of responses and variance analysis the evaluation of the effects and the significance of the models were accomplished for the variables of responses, biodiesel yield in mass and the content of esters. The regression of the methyl biodiesel for ANOVA appropriately explained at the level of 95%, the variation of the data (R2 = 0,78224, for yield biodiesel and R2 = 0,9090, for the content of esters). The yield in mass above 94% are were obtained with following conditions: ratio oil:methanol in the strip 1:7 and 1:9, concentration KOH below 1,5% and reaction time below 60 seconds. The yield the content of esters above 98% with following conditions: ratio oil:methanol in the strip 1:5 and 1:10, concentration KOH above 1,4% and reaction time above 40 seconds.